La señora Macbeth: The Price Paid for Blind Love and Silent Complicity - Nigro, Kirsten F. (Latin American Theatre Review, 2018)
Griselda Gambaro’s La señora Macbeth (2003) is not so much an adaptation, appropriation or retelling of Shakespeare’s source text as it a complex hybrid of all three approaches. Gambaro places Lady Macbeth front stage; her famous husband remains off stage, although he is still a lingering presence in the play. Lady M, as she is called in Gambaro’s written play text, does not thirst for power but rather for her husband’s love. While she is not the prime mover in Macbeth’s murderous acts, she assumes his guilt, refusing to believe him capable of such crimes. Such is her love that Lady M speaks through Macbeth, speaking his words as written in Shakespeare’s text. This leaves her voiceless, resulting in a silence that renders her complicit in his bloodletting. As in so many of her plays, Gambaro works here by allusion and metaphor; Lady M’s not seeing and not speaking out are reminiscent of another time and place—Argentina during the Dirty War. Gambaro has allowed for this interpretation, but, as the witches in La señora Macbeth predict, there will be women in the future who are not blinded by love and who do make their voices heard.